PSYCHOPEDAGOGICAL WORK IN THE DEVELOPMENT OF STUDENTS - Mateus Calgarotto, Vitor (Revista Gênero e Interdisciplinaridade, 2023)
In this document we seek to justify through literature all the issues that underlie psychopedagogical work, with the aim of enriching information on the subject and highlighting the importance of the Psychopedagogue, a professional who is fundamental in educational institutions, with his role being essential both in the sector pedagogical, but also social, occupying a unique place in terms of health and education. Psychopedagogy is comprehensively concerned with learning, considering several factors, such as: educational, physical, emotional, psychological, also analyzing all niches that can contribute positively and negatively to the interpersonal development of children, also including sociocultural issues, which they are shaped by the nucleus where the child develops. Otherwise, the professional highlights points that could harm students in their studies and creates methods that can highlight their protagonism, thus enabling their total satisfaction as a learner, and making them protagonists of the teaching-learning process.